Relative Contributions of Halobacteriovorax and Bacteriophage to Bacterial Cell Death under Various Environmental Conditions - Huan Chen (American Society for Microbiology, 2018)
ABSTRACT The role of protists and bacteriophages in bacterial predation in the microbial food web has been well studied. There is mounting evidence that Bdellovibrio and like organisms (BALOs) also contribute to bacterial mortality and, in some cases, more so than bacteriophages. A full understanding of the ecologic function of the microbial food web requires recognition of all major predators and the magnitude of each predator’s contribution. Here we investigated the contribution of Halobacteriovorax, one of the BALOs, and bacteriophages when incubated with their common prey, Vibrio vulnificus, in a seawater microcosm. We observed that Halobacteriovorax was the greatest responder to the prey, increasing 18-fold with a simultaneous 4.4-log-unit reduction of V. vulnificus at 40 h, whereas the bacteriophage population showed no significant increase. In subsequent experiments to formulate a medium that would support the predatory activities and replication of both predators, low-nutrient media favored the predation and replication of the Halobacteriovorax, whereas higher-nutrient media enhanced phage growth. The greatest prey reduction and replication of both Halobacteriovorax and phage were observed in media with moderate nutrient levels. Additional experiments show that the predatory activities of both predators were influenced by environmental conditions, specifically, temperature and salinity. The two predators combined exerted greater control on V. vulnificus, a synergism that may be exploited for practical applications to reduce bacterial populations. These findings suggest that along with bacteriophage and protists, Halobacteriovorax has the potential to have a prominent role in bacterial mortality and cycling of nutrients, two vital ecologic functions. IMPORTANCE Although much has been reported about the marine microbial food web and the role of micropredators, specifically viruses and protists, the contribution of Bdellovibrio-like predators has largely been ignored, posing a major gap in understanding food web processes. A complete scenario of the microbial food web cannot be developed until the roles of all major micropredators and the magnitude of their contributions to bacterial mortality, structuring of microbial communities, and cycling of nutrients are assessed. Here we show compelling evidence that Halobacteriovorax, a predatory bacterium, is a significant contributor to bacterial death and, in some cases, may rival viruses as agents of bacterial mortality. These results advance current understanding of the microbial loop and top-down control on the bacterial community.